PERSEPSI DAN SEMIOTIKA TATO PADA MAHASISWA DI KOTA PADANG - YOSI PRANA DEWI, Ir. Drs. Heldi, M.Si, Drs. Wisdiarman, M.Pd (Serupa The Journal of Art Education, 2014)
This research aims to have the understanding of: 1) Students perseptions of tattoos 2) Students semiotics on tattoos in the city of Padang. The subject of that research was about students from various Padang’s Universities which includes UNP, UNAND, UBH and UPI using Qualitative descriptive research methods. Data’s collection from that research was done through observation technique, Interviews, and (photos) documentation. Students perceptions towards tattoos are basically positive as well as negative. From a positive point of view, tattoos could be use as an identity or represent an expresisions of the owner’s feelings. On the negative side, tattoos could be identified with Premanism or rebellious people which one part are used by young people such as Punk, Rock and Metal. Other than that tattoss are forbidden the Islam religion. 2) Semiotics tattoos on students varies based on the existence like Qualisign, Sinsign and Legisign. Based on relations such as: Icon, Index and Symbols. Build on relations such as Syntatic semiotics, Syntatics semiotic and Pragmatic semiotic.Keywords: Perception, Semiotics tattoos, University students